High‐density polyethylene reinforced by low loadings of electrochemically exfoliated graphene via melt recirculation approach. Issue 20 (7th January 2021) - Bansala, Taruna; Verma, Pawan; Vashisth, Aniruddh; Hope, Joshua T.; Yakovlev, Sergey; Uppili, Sundararajan; Green, Micah J.; Hule, Rohan A.
Abstract: The purpose of the paper is to demonstrate the effectiveness of high‐aspect ratio electrochemically exfoliated graphene (EEG) as a filler in high‐density polyethylene (HDPE); we use an industrially viable polymer processing technique (melt blending with melt recirculation) to ensure excellent dispersion and reinforcement at low loadings. The effects of nanofiller loading were evaluated for two different HDPE grades with two different melt flow indices (MFI) based on crystallization, tensile, and rheological properties. The findings indicate improvements in mechanical properties (tensile modulus and tensile strength) for all HDPE/EEG nanocomposite samples; however, the reinforcement was more pronounced at 0.2 wt% loading, indicating a transition from excellent dispersion at lower loadings to aggregated at higher loadings. The low and high MFI HDPE/EEG nanocomposites at 0.2 wt% EEG loading displayed an improvement of 31% and 40% in tensile modulus and 19% and 33% in tensile strength, respectively. The improved mechanical response with higher MFI nanocomposites is likely due to enhanced dispersion associated with the lower melt viscosity. Similarly, the rheological results also showed maximum increase in storage and loss modulus at a loading of 0.2 wt% EEG. In conclusion, EEG can be an effective filler if proper dispersion is achieved, which is challenging at high loadings. Abstract :